Effect of Two Different Medias on Selected Liberica Coffee Clones Stem Cuttings Performance - Ismail, Ahmad; Ismail, Khairol; Pa'ee, Furzani; Abd Rani, Muhammad Naim Fadzli; Muhamad Nor, Azlan Azizi; Awang, Mohd Rani (Journal of Sustainable Natural Resources, 2025)
Coffee production in Malaysia has been declining, and the demand for high-quality coffee is increasing. To address this issue, Malaysian Agricultural Research and Development Institute (MARDI) has released new coffee clones, MKL 8, 9, and 10 with promising yield quality. Under current guidelines, planting materials must be produced through grafting, but huge drawback are the time needed to produce matured planting materials. A new potential technique was developed and could save a lot of time and this technique is known as stem cuttings was studied using standard media sand and soil (1:1). Therefore, study aimed to evaluate the effects of two different media on the vegetative performance of stem cuttings on selected clone MKL 8, 9 and 10 was carried out. The experiment was conducted using a randomized complete block design with a factorial arrangement with five replications. The results showed that the type of media significantly affected root fresh weight and root dry weight, with media 1 (soil, peat moss, and sand in a ratio of 4:2:1) performing better than media 2 (soil, sand, and CIRP in a ratio of 4:4:1). The clones also exhibited significant differences in SPAD meter readings, height, and leaf number, with MKL 8 performing better than MKL 9 and MKL 10. Correlation analysis revealed that SPAD readings were positively associated with leaf number and survival, while plant height was positively associated with leaf number, survival, fresh root weight, and dry root weight. This study highlights the importance of selecting suitable clones and media for coffee stem cuttings to ensure better performance and improve coffee production in Malaysia.